Design and Optimization of Transparent Antennas for Repeater-Assisted MIMO Systems for Solar Panel Integration - Bocigas Iglesias,Julia Patricia (2025)
Antennas are fundamental components in the evolution of wireless communication systems, including current 5G networks and emerging 6G technologies. This thesis presents the design, simulation, and experimental validation of two antennas specifically developed for integration into repeater-assisted MIMO (Multiple Input Multiple Output) systems. These systems aim to enhance spatial multiplexing and coverage by employing distributed, low-complexity repeater nodes that act as active scatterers, retransmitting signals with minimal latency and without relying on dedicated backhaul connections. The proposed antennas are designed for conformal deployment on cylindrical solar panel surfaces, enabling compact, energy-autonomous communication nodes. This integration supports flexible and cost-effective deployment of repeater-assisted MIMO in scenarios where conventional infrastructure is impractical, such as in coverage holes, indoor or obstructed environments, or locations lacking reliable backhaul connectivity. This work investigates two complementary antenna designs: a directive equiangular spiral antenna array for focused backhaul communication, and a transparent omnidirectional antenna array for uniform azimuthal coverage. Both designs are optimized for conformal integration, with special attention to minimizing mutual coupling, achieving impedance matching, maintaining high radiation efficiency, and preserving polarization purity. The proposed antennas are evaluated through comprehensive full-wave electromagnetic simulations and validated via experimental measurements. Key performance metrics such as gain, bandwidth, impedance matching, polarization, and isolation are assessed under realistic conformal mounting conditions. The results confirm that both antennas exhibit robust performance when integrated onto curved photovoltaic surfaces, supporting their suitability for next-generation solar-powered repeater nodes. By enabling efficient, low-profile, and scalable antenna solutions, this thesis advances the development of repeater-assisted MIMO architectures, offering a promising foundation for sustainable and flexible wireless infrastructure in future 5G and 6G networks.
Keywords: Directive antenna; Omnidirectional antenna; Repeater-assisted MIMO; Conformal antenna; Cylindrical integration; Solar-powered repeater; Electromagnetic simulation.